Temporary Mechanical Circulatory Support: Left, Right, and Biventricular Devices - Dangl, Michael; Albosta, Michael; Butros, Hoda; Loebe, Matthias (Current Cardiology Reviews, 2023)
Temporary mechanical circulatory support (MCS) encompasses a wide array of invasive devices, which provide short-term hemodynamic support for multiple clinical indications. Although initially developed for the management of cardiogenic shock, indications for MCS have expanded to include prophylactic insertion prior to high-risk percutaneous coronary intervention, treatment of acute circulatory failure following cardiac surgery, and bridging of end-stage heart failure patients to more definitive therapies, such as left ventricular assist devices and cardiac transplantation. A wide variety of devices are available to provide left ventricular, right ventricular, or biventricular support. The choice of a temporary MCS device requires consideration of the clinical scenario, patient characteristics, institution protocols, and provider familiarity and training. In this review, the most common forms of left, right, and biventricular temporary MCS are discussed, along with their indications, contraindications, complications, cannulations, hemodynamic effects, and available clinical data.
Keywords: cardiogenic shock